Novel Variant in Exon 3 of the BMP4 Gene Resulted in Ectopic Posterior Pituitary, Craniocervical Junction Dysmorphism and Limb Anomaly. (19th May 2022) - Calcaterra, Valeria; Lamberti, Rossella; Viggiano, Claudia; Baldassarre, Paola; Spaccini, Luigina; Alfano, Rosa Maria; Izzo, Giana; Valentini, Laura Grazia; Zuccotti, Gianvincenzo
Abstract : Introduction . Pituitary differentiation involves a large number of transcription factors. In particular, BMP4 expression is fundamental for pituitary gland commitment from the ventral diencephalon, suppressing Shh expression in Rathke's pouch. Pathogenic variants in BMP4 are reported in the literature with a broad phenotypic spectrum, including pituitary and brain malformations. Case Presentation . A five-year-old girl came to medical attention following a mild cervical trauma with onset of cervical pain. On clinical examination at birth, postaxial polydactyly type B of the left hand was observed and removed at 10 months of age. A cervical radiography was performed, and a suspicion of craniocervical junction malformation was made. A magnetic resonance imaging of the cervical spine was made, showing an ectopic posterior pituitary, associated with dysmorphism of the craniocervical junction. The anthropometric parameters were pubertal Tanner stage 1, weight 16 kg (z-score: −1.09), height 107 cm (z-score: −0.76), and BMI 14 kg/m 2 (z-score: −0.92). Normal hormonal assessment was detected. Genetic analysis via next generation sequencing showed a novel de novo heterozygous variant (c.277 G > T, p.Glu93 ∗ ) in exon 3 of BMP4 . Discussion . We described a novel mutation in BMP4, resulting in ectopic posterior pituitary with normal hormonal assessment, associated to craniocervical junction dysmorphism and limb anomaly. It is important to monitor patient's growth and puberty and to screen the onset of symptoms related to the deficiency of one or more anterior as well as posterior pituitary hormones.